Pengaruh Influencer Instagram Marketing Lokal Terhadap Niat Beli Masyarakat pada Produk Es Teler Sultan Jember - Ichwan Zarkasi Brillyano Gunawan; Neviyani Neviyani; Moh Usman Kurniawan (Relasi : Jurnal Ekonomi, 2024)
The aim of this research is to determine the influence of local Instagram marketing Influencer  s on people's purchase intentions for Es Teler Sultan Jember products. This research uses a quantitative research approach. The type of data collection from research uses documentation and questionnaires. Meanwhile, data analysis uses validity, reliability, normality and Simple Linear Regression Analysis tests. The researcher tested the hypothesis using Simple Linear Regression Analysis because this research was conducted to determine the influence of Local Instagram Marketing Influencer  s (X) on consumer Purchase Intentions (Y). This test technique is used to test and find out whether individual independent variables have a significant influence on the dependent variable. If the calculation results show that Sig < alpha 0.05 (SPSS Release 20.0 for Windows). The normality test using the Kolmogrov-Smirnov method was significant at 0.389 > 0.05. The regression method in this research has met the normality assumption. The correlation value is 0.346. From this output, a coefficient of determination (R Square) of 0.121 was obtained. The influence of the independent variable (Local Instagram Marketing Influencer  s) on the dependent variable (Purchase Intention) is 21.5%. In the ANOVA test, the calculated F value was obtained = 9.524 with a significance level of 0.000 <0.05. So the regression model can be used to predict the participation variable or in other words the influence of the Local Instagram Marketing Influencer   variable (X) on the Purchase Intention variable (Y). Based on the significant value from the Coefficients table, a significant value of 0.000 < 0.05 is obtained, so it can be concluded that the Local Instagram Marketing Influencer   variable (X) is related to the Purchase Intention variable (Y), the calculated t value is 2.724 > t Table 2.008, so it can be concluded that the Instagram Marketing variable Local (X) influences the Purchase Intention variable (Y).